LEGAL CONFLICT DURING MARTIAL STATE: WHO IS RESPONSIBLE FOR EXCESS OF POWER? - Soroka, Larysa (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is a comprehensive study of current issues concerning the functioning of public authorities under martial law in Ukraine, focusing on the legal analysis of the authorities exceeding their powers. Research methods include document analysis and synthesis, cognitive-analytical methods, as well as systematization and generalization. The research results showed that the introduction of a special legal regime during an armed conflict objectively requires a temporary expansion of the powers of state authorities to effectively respond to threats to national security, maintain public order, and ensure defense capability. However, this very expansion creates increased risks of exceeding the permissible limits of interference in citizens’ rights, manipulation of the notion of ‘military necessity,’ and the emergence of legal nihilism. Analyzing the provisions of current legislation, one can draw an unequivocal conclusion: territorial recruitment and social support centers do not have the authority to independently detain individuals, even in cases of evasion of mobilization obligations. Their functions are limited to organizational and supervisory measures in the areas of military registration, mobilization, and social support. Discussion: in a state of war, it is important to maintain a balance between the needs of national security and the guarantees of citizens’ rights and freedoms, which continue to apply even in extraordinary circumstances. The legality of the actions of public authorities remains a defining criterion in a rule-of-law state, and deviation from this principle leads to a loss of public trust and an increase in legal nihilism.